Investigating the genetic basis of vertebrate dispersal combining RNA ‐seq, RAD ‐seq and quantitative genetics - Luis M. San‐Jose; Elvire Bestion; Félix Pellerin; Murielle Richard; Lucie Di Gesu; Jordi Salmona; Laurane Winandy; Delphine Legrand; Camille Bonneaud; Olivier Guillaume; Olivier Calvez; Kathryn R. Elmer; et al. (Molecular Ecology, 2023)
Although animal dispersal is known to play key roles in ecological and evolutionary processes such as colonization, population extinction and local adaptation, little is known about its genetic basis, particularly in vertebrates. Untapping the genetic basis of dispersal should deepen our understanding of how dispersal behaviour evolves, the molecular mechanisms that regulate it and link it to other phenotypic aspects in order to form the so‐called dispersal syndromes. Here, we comprehensively combined quantitative genetics, genome‐wide sequencing and transcriptome sequencing to investigate the genetic basis of natal dispersal in a known ecological and evolutionary model of vertebrate dispersal: the common lizard, Zootoca vivipara. Our study supports the heritability of dispersal in semi‐natural populations, with less variation attributable to maternal and natal environment effects. In addition, we found an association between natal dispersal and both variation in the carbonic anhydrase ( CA10 ) gene, and in the expression of several genes ( TGFB2 , SLC6A4 , NOS1 ) involved in central nervous system functioning. These findings suggest that neurotransmitters (serotonin and nitric oxide) are involved in the regulation of dispersal and shaping dispersal syndromes. Several genes from the circadian clock ( CRY2, KCTD21 ) were also differentially expressed between disperser and resident lizards, supporting that the circadian rhythm, known to be involved in long‐distance migration in other taxa, might affect dispersal as well. Since neuronal and circadian pathways are relatively well conserved across vertebrates, our results are likely to be generalisable, and we therefore encourage future studies to further investigate the role of these pathways in shaping dispersal in vertebrates.

Dispersal syndromes in challenging environments: A cross‐species experiment - Julien Cote; Maxime Dahirel; Nicolas Schtickzelle; Florian Altermatt; Armelle Ansart; Simon Blanchet; Alexis S. Chaine; Frederik De Laender; Jonathan De Raedt; Bart Haegeman; Staffan Jacob; Oliver Kaltz; et al. (Ecology Letters, 2022)
Dispersal is a central biological process tightly integrated into life‐histories, morphology, physiology and behaviour. Such associations, or syndromes, are anticipated to impact the eco‐evolutionary dynamics of spatially structured populations, and cascade into ecosystem processes. As for dispersal on its own, these syndromes are likely neither fixed nor random, but conditional on the experienced environment. We experimentally studied how dispersal propensity varies with individuals' phenotype and local environmental harshness using 15 species ranging from protists to vertebrates. We reveal a general phenotypic dispersal syndrome across studied species, with dispersers being larger, more active and having a marked locomotion‐oriented morphology and a strengthening of the link between dispersal and some phenotypic traits with environmental harshness. Our proof‐of‐concept metacommunity model further reveals cascading effects of context‐dependent syndromes on the local and regional organisation of functional diversity. Our study opens new avenues to advance our understanding of the functioning of spatially structured populations, communities and ecosystems.